The development of the mathematical model of an RPV and an investigation on the use of an EKF for the identification of its aerodynamic derivatives - Milonidis, E. (Cranfield University, 1987)
A six-degrees of freedom mathematical model of an experimental Remotely Piloted Vehicle (RPV) and the linearised longitudinal and lateral models at 30 m/sec are developed. The longitudinal and lateral dynamics are analysed and the equivalent discrete systems are used to provide baseline data for the identification of the aerodynamic derivatives of the RPV. An advanced aircraft parameter estimation method - the Extended Kalman F ilte r - is implemented for the estimation of the aerodynamic characteristics of the RPV. Conclusions are drawn about the id e n tifi- a b ility of the s tab ility and control derivatives from pitch, roll and yaw rate measurements.